Bureaucratisation Of Codified Project Management Practices And Its Impact On Project Performance Within Malaysian Construction And Property Development Industries. - Ng, Sin Hong (2021)
In recent decades, the emphasis on project management activities has expanded substantially, perceived as a method to enhance project performance. Such rapid evolution has inevitably led to two opposing points of view, with some researchers found the usual methods of prefixed rules and regulations to be a bureaucratisation of management styles in the Weberian tradition that improves project performance. In contrast, other scholars have a different view, believing that the bureaucratisation of project management is flawed and can negatively impact the performance of project managers. The two rising differences of opinion have led to the development of project management practices becoming an exciting field for investigation and offers diverse views as to whether project management practices should be fluid or comply with specific structured disciplines. This thesis aims to explores how the bureaucratisation of codified project management practices are relevant to project performance, with a specific investigation of the construction and development industries in Malaysia. The competency components of the codified project management practices are taken from the summary of the five well-known project management institutions where 10 competency components been chosen. The participants in this study are project managers in Malaysia's construction and development industries. A total of 210 questionnaires were distributed, and 194 questionnaires were received. The notable finding is that all the 10 competency components display bureaucracy with formalisation of five competency components (PSM, PTM, PCM, PQM & PCOMM) and centralisation of another set of five competency components (PTM, PCM, PQM, PHRM & PRM) showing a significant, and positive relationship to project performance. The findings can serve as a guidance to Malaysia’s construction and development industries which of the 10 competency components should be made bureaucracy, i.e., high formalisation and high centralisation for the enhancement of the project performance. Identifying other project performance enablers and examining their effects could be possible for future research. This study may be replicated in future investigations, and larger samples may be used in different contexts, such as in different developing or developed countries with more in-depth and more vibrant research.